2015
DOI: 10.1002/etc.2969
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the cytotoxic impact of chlorfluazuron on selected insect and human cell lines

Abstract: To gain new insight into the mechanism of selective cytotoxicity of benzoylureas as insecticides, the in vitro mode of action of chlorfluazuron was investigated on lepidopteran Tn5B1-4 and Sf-21 cells and human Hek293 and HepG2 cells. Chlorfluazuron inhibited the proliferation of Tn5B1-4 and Sf-21 cells with 50% inhibitory concentration values (IC50) of 4.96 µM and 1.12 µM at 48 h and 2.37 µM and 1.76 µM at 96 h, respectively, versus that of Hek293 and HepG2 cells with IC50 values >20 µM. When transferred to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, it appears that avoiding the perimeter wells provided consistency, presumably by reducing evaporation influences 48 . Huang et al 55 . also reported that measuring growth inhibition and mortality of insect and human cells separately can elucidate a compound's mode‐of‐action as a retardant of growth rather than by cytotoxic means.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it appears that avoiding the perimeter wells provided consistency, presumably by reducing evaporation influences 48 . Huang et al 55 . also reported that measuring growth inhibition and mortality of insect and human cells separately can elucidate a compound's mode‐of‐action as a retardant of growth rather than by cytotoxic means.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we used D.mel ‐S2 cell lines to assess the reliability of an additional cell line, Sf9, in response to known insecticides of both a natural and nature‐equivalent, synthetic sources. In general, these insect cell lines have been shown to be useful in the elucidation of many insecticidal modes of action, 55, 76 since they offer a direct access to target sites that may otherwise be difficult to access in whole insect assays, or for pesticides whose efficacy may be compromised by biological activities such as physical exclusion, excretion, metabolic detoxification or cellular degradation 14 . However, careful consideration should be given to the appropriateness of each cell line and its ‘fit for purpose’ based on source tissue, for example embryonic, midgut or ovarian origin and their innate membrane properties 76 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation